Fit2 fat 2fit : the unexpected lessons from gaining and losing 75 lbs on purpose - Manning, Drew (HarperOne, 2012)
The author, a longtime personal trainer and admitted fitness addict, has never been overweight. So he decided to learn what millions of Americans, and many of his clients, live with every day. For six months, he stopped exercising and ate common American diet of fast food and processed snacks. This title describes all the details of that journey.